Glucocorticoid‐Induced Leucine Zipper Governs the Therapeutic Potential of Mesenchymal Stem Cells by Inducing a Switch From Pathogenic to Regulatory Th17 Cells in a Mouse Model of Collagen‐Induced Arthritis. Issue 6 (June 2015) - Luz‐Crawford, P.; Tejedor, G.; Mausset‐Bonnefont, A. L.; Beaulieu, E.; Morand, E. F.; Jorgensen, C.; Noël, D.; Djouad, F.
<x xml:space="preserve">Abstract</x> Objective Mesenchymal stem cells (MSCs) are potent immunosuppressive cells that have shown promise in the treatment of rheumatoid arthritis (RA). Deciphering the intrinsic characteristics of MSCs that correlate with their biologic activity will facilitate their clinical use. Recently, the role of glucocorticoid‐induced leucine zipper (GILZ) in the development of RA has been documented. The aim of this study was to evaluate whether GILZ expression by MSCs may contribute to their therapeutic effect. Methods MSCs were isolated from GILZ‐deficient (GILZ−/−) mice and wild‐type mice. MSCs (1 × 106 cells) were injected twice via the tail vein into mice with collagen‐induced arthritis (CIA). Results In vitro, we showed that GILZ is a key factor involved in the immunosuppressive potential of MSCs. MSCs derived from GILZ−/− mice did not suppress the proliferation of CD4+ T cells and were less efficient than MSCs derived from WT mice in altering Th17 cell polarization. Thus, we investigated the role of GILZ in an experimental model of arthritis and demonstrated that although WT MSCs significantly reduced paw swelling in arthritic mice, GILZ−/− MSCs did not. Moreover, the magnitude of the effects of GILZ−/− MSCs on Th17 cell frequency was significantly lower than that of WT MSCs. The therapeutic effect of MSCs correlated with the generation of Treg cells bearing the CD4 + RORγt+IL‐17low IL‐10+ signature, and Th17 cell polarization was GILZ dependent. Conclusion This study demonstrates that GILZ has an essential role in the therapeutic effectiveness of MSCs in arthritis by favoring Th17 cell polarization toward a regulatory phenotype. Therefore, potentiation of GILZ expression in MSCs could represent a means to enhance their therapeutic effect in autoimmune diseases.